Community Mapping And Health Seeking Practices Among Residents of an Indonesian Village - Wisnu Probo Wijayanto; Ida M. Dela Cruz (Universitas Aisyah Pringsewu, 2023)
The purpose of the study was to do community mapping and know the health- seeking practices among residents of an Indonesian village. Health- seeking practices is an important modifiable behavior which can be enhanced through knowledge by describing the most common causes of mortality and morbidity among the residents of an Indonesian village. The study utilized descriptive survey design to investigate the health beliefs, healthy eating culture, and health seeking practices among residents of Lampung Province. Based on the data, the community health belief value of Lampung Province is 2.750 with the category of moderate. The value of health eating culture is 2.945 (moderate). Based on this data the people have a healthy-eating culture which is categorized as moderate. The value of health-seeking practices was 2.95 (moderate), meaning that people in Lampung have health seeking practices that is categorized as average. Coverage of clean and healthy lifestyle in Lampung Province in the year 2022 has resulted to 59.2%. A positive local outlook on life is essential to wellness and each fulfilled the indicators. A “well” person is satisfied in his work, is spiritually fulfilled, enjoy leisure time, physically fit, socially involved and has a positive emotional and mental outlook.